Smart Contracts - Fries, Martin (Mohr Siebeck, 2019)
How smart are smart contracts? Do they live up to their promise of a more effective rights enforcement? Nine pioneers from both academia and legal practice discuss the technological and legal foundations of smart contracts, provide practical examples, and debate their impact on the judicial system.